Monitoring the moin beach to control morphological changes due the construction of the moin container terminal, Limon - Alfaro Chavarría, Henry Gustavo (2016)
The Moin Container Terminal (MCT) is a project under construction that represents one of the largest investments in Latin American port facilities. The first stage consists of a seven million cubic meter sand fill constructed using dredged material, a 1.5 kilometer breakwater, a 600 meter and two berth quay with a draft of 14.5 meter, a 16 meter deep approach channel and the placement of six gantry cranes. The MCT is located in the Caribbean coast of Costa Rica, specifically in Moin, next to the existing port facilities, where the coastline is straight and perpendicular to the direction of the most frequent waves that affect the area. Due to the geometry of the project, its location and interaction with the morphodynamics of the site, a series of periodic survey profiles were carried out with a echosounder and drone-based flights in order to assess changes occurring during the project implementation, on the stretch of beach occupied by the project. This paper encompasses the results obtained up to date, which combine monthly based changes in the coastline obtained using photogrammetric techniques, 250 meter resolution bathymetric profiles in the area of the project, bathymetric surveys in the fill zone and wave information